Pengaruh Distinctive Capabilities dan Integrated Marketing Communication Terhadap Citra Destinasi Wisata Maritim Pulau Weh - Cut Devi Maulidasari; Yusnaidi Yusnaidi (Universitas Teuku Umar, 2018)
Abstract : The number of foreign tourists who come to Sabang do not increase in the last 3 years. In 2011, foreign tourists who came to Sabang amounted to 5,055 people. But the next year dropped to about 4,622 people. In 2013, while it increased but the increase is very small. This indicates a lack of foreign tourists decision to decide maritime tourist destinations in Sabang as one destination tourist destinations. Low-making visit is not independent of the image is less strong maritime tourist destinations in Sabang as one of the tourist destinations are worth a visit by tourists.The objective of this study is to analyze the impact of distinctive capabilities and integrated marketing communication to the image of Weh Island tourist destination.Sampel in this study were 160 tourists who had visited Sabang. Testing this hypothesis is to analyze the value of Critical Ratio (CR) and the Probability (P) if the results of the data, compared with the required statistical limits, ie above 1.96 for the value of CR and below 0.05 for the value of P (probability). Of 5 verificatif hypotheses are tested, all of them passed the test by using two criteria exist. Then to 5 of this hypothesis is accepted. In other words, there is a significant influence between the variables tested, both associated with an intervening variable and dependent. Keywords: Distinctive Capabilities, Integrated Marketing Communication, Destinations Image , Decision to Visit, Maritime Travel Destinations, Pulau Weh.